Tobacco: a future disaster for Turkey’s children - Crofton, John (The Turkish Journal of Pediatrics, 1996)
Limited data from Turkey indicate that smoking presents a major threat to Turkish children. Parental, particularly maternal, smoking results in an increase in spontaneous abortion, low birth weight, congenital abnormalities, neonatal death and decreased physical and mental development in the infant, which can persist into adult life. Parental smoking results in increased rates of respiratory and middle ear illness in children, more so in infants and in older children more school absences. Naturally both of the effects are even greater if the children start to smoke themselves. Smoking parents are more likely to have smoking children, so that the cycle of illness repeats in future generations. Doctors have a major responsibility to save both present and future generations from this disaster. In this article appropriate action is outlined.